2021
DOI: 10.3389/fimmu.2021.676232
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Microbiota—A Promising Target for Antiviral Therapy?

Abstract: The intestinal microbiota is thought to be an important biological barrier against enteric pathogens. Its depletion, however, also has curative effects against some viral infections, suggesting that different components of the intestinal microbiota can play both promoting and inhibitory roles depending on the type of viral infection. The two primary mechanisms by which the microbiota facilitates or inhibits viral invasion involve participation in the innate and adaptive immune responses and direct or indirect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 163 publications
0
21
0
1
Order By: Relevance
“…It would appear that another reason why severe COVID-19 is dangerous for patients may lie in the significant loss of appetite. A certain relationship has been observed between appetite loss and calorie reduction in mice and a significant increase in the ratio of Bacteroidetes to Firmicutes abundance, which was also noted in a study of microbiota alterations during respiratory viral infection [103,125]. The reduction of energy intake from food (which is observed in COVID-19 patients due to significant loss of appetite) may contribute to worsening their condition [126].…”
Section: Microbiota In Covid-19mentioning
confidence: 79%
See 2 more Smart Citations
“…It would appear that another reason why severe COVID-19 is dangerous for patients may lie in the significant loss of appetite. A certain relationship has been observed between appetite loss and calorie reduction in mice and a significant increase in the ratio of Bacteroidetes to Firmicutes abundance, which was also noted in a study of microbiota alterations during respiratory viral infection [103,125]. The reduction of energy intake from food (which is observed in COVID-19 patients due to significant loss of appetite) may contribute to worsening their condition [126].…”
Section: Microbiota In Covid-19mentioning
confidence: 79%
“…Another controlled study in mice demonstrated that viral lung infection leads to unfavorable alterations in gut microbiota composition, manifesting with an increase in Bacteroidetes and decrease in Firmicutes abundance [102]. Gut microbiota may be a promising target for viral infection therapy [103,104]. Notably, gut microbiota (depending on its composition and activity) may both promote or prevent viral infections by regulating the immune response [103].…”
Section: Microbiota In Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…In the process of viral invasion, the intestinal microbiota plays a key role, acting as a barrier, interacting directly or indirectly with the virus, and stimulating the innate and adaptive immune responses. Viral infections also have the potential of changing the composition of the gut microbiota [ 11 ]. Indeed, during COVID-19, modifications in microbiota composition have been reported [ 12 , 13 , 14 , 15 ].…”
Section: Microbiota and Covid-19mentioning
confidence: 99%
“…In addition, the spread of COVID-19 disease worldwide has prompted investigation into how to deal with viral infections that also have the potential of changing the composition of the gut microbiota [ 11 ], influencing cardiac health [ 10 ].…”
Section: Introduction: Microbiota and The “Heart–gut Axis”mentioning
confidence: 99%